Poe, Fuller, and the mesmeric arts transition states in the American Renaissance - Mills, Bruce, 1958- (University of Missouri Press, 2005)
"Examines how the writings of Edgar Allan Poe and Margaret Fuller draw from representations of and theories concerning animal magnetism, somnambulism, or hypnosis rendered in newspapers, literary and medical journals, pamphlets, and books, and also includes discussion of Ralph Waldo Emerson, Lydia Maria Child, and Walt Whitman"--Provided by publisher.